A cross-sectional study of factors underlying the risk of female nurses' suffering abuse by their partners Estudio transversal sobre factores de riesgo de sufrir violencia por compañero íntimo en la mujer enfermera Estudo transversal sobre fatores de risco de violência por parceiro íntimo entre enfermeiras - María-Aurora Rod; Manuel Vaquero-Abellán; Liana Bertagnolli da Rosa (Universidade de São Paulo, 2012)
This study aimed to identify factors underlying the risk of suffering abuse by a partner. A cross-sectional study of 622 female nurses was accomplished, randomly chosen at their place of work, at a hospital and health centers. We used a self-administered validated questionnaire that covered psychological, physical and sexual abuse, complemented by a set of sociodemographic questions. The nurses at most risk of being abused by their partners were those who supported their family by their own salary (Odds Ratio: 2.41 [0.63-9.15]), those who lived with dependents (Odds Ratio: 4.27 [1.43-2.78]) and had a partner from social class IIIa (Odds Ratio: 2.62 [1.37-5.00]). The data appear to indicate financial independence as a risk factor for this type of abuse. Se tuvo por objetivo investigar los factores de riesgo relacionados al maltrato por compañero íntimo. Se trata de un estudio transversal realizado en 622 enfermeras, elegidas por aleatorización de sus lugares de trabajo, Hospitales y Centros de Salud. Se utilizó un cuestionario autoadministrado sobre maltratos psicológico, físico y sexual, complementado con preguntas de carácter sociodemográfico. Las mujeres enfermeras con mayor probabilidad de sufrir violencia del compañero íntimo fueron las que mantienen la familia con su salario (Odds Ratio: 2,41 [0,63-9,15]), las que conviven con hijos (Odds Ratio: 4,27 [1,43-2,78]) y las con pareja de clase social IIIa (Odds Ratio: 2.62 [1.37-5.00]). Se concluye que los datos parecen indicar que la independencia constituye un riesgo de maltrato. O objetivo deste estudo foi identificar os fatores de risco de abuso por parceiro íntimo entre enfermeiras. Trata-se de estudo transversal, realizado com 622 enfermeiras, selecionadas aleatoriamente nos seus locais de trabalho (hospitais e centros de saúde). Utilizou-se um questionário autoadministrado sobre maus-tratos psicológico, físico e sexual, complementado com perguntas de caráter sociodemográfico. As mulheres enfermeiras com maior probabilidade de sofrer violência foram: aquelas que mantinham a família com seu salário (Odds Ratio: 2,41 [0,63-9,15]), as que conviviam com filhos (Odds Ratio: 4,27 [1,43-2,78]) e com parceiro íntimo de classe social IIIa (Odds Ratio: 2.62 [1.37-5,00]). Os dados parecem indicar que a independência representa fator de risco para esse abuso.